Sim, sou um negro de cor: Wilson Simonal e a afirmação do orgulho negro no Brasil dos anos 1960 - Bruno Vinicius Leite de Morais (2016)
In the context of the 1960s and 1970s, it is considered that the left-wingers, away from politics, had a prominent role in the artistic field, through the so-called activist art. When it comes to activist music, two groups are usually highlighted by scholars of the period: the national-popular and the Tropicalist. The aim of this dissertation is to discuss, in the figure of the politically controversial and conservative singer Wilson Simonal, a third type of political activity that, in the 1960s, was apparently overshadowed by the other two: the claim for racial equality, echoing the international mobilization against the prejudice of black people. So, our proposal is to situate and relate the music production of Simonal between 1963 and 1971, with the manifestations of the Black Pride that emerged in several regions of the world in the same period of time. This is to contribute to identify, through the New Political History, cultural events related to the affirmation of black identity and the claim for "racial " equality, fighting prejudice and inferiority ideas against black people. For this, we try to relate the specific context of the national reality, which was facing the military dictatorship, with the international manifestations of the racial cause, analyzing the song played in the phonogram, as a privileged vehicle for the movement of such messages.